Virtual acoustic reconstruction of a lost church: application to an Order of Saint Jerome monastery in Alzira, Spain. Issue 3 (4th May 2018) - Sender, M.; Planells, A.; Perelló, R.; Segura, J.; Giménez, A.
Abstract : Archaeological acoustics is the study of ancient environments that were used for performances. The combination of this study with room acoustics enables us to study the acoustic evolution of existing buildings, and make reconstructions of rooms that were destroyed or are in a poor state of conservation. This work presents the virtual acoustic reconstruction of the fourteenth century church of the Jeromite monastery of Santa Maria de la Murta in Alzira, Spain. It was abandoned in 1836 and is now in ruins. The work develops a geometrical model for acoustic simulation, together with a description of the building materials as taken from the historical documents, and an acoustic study of the church. Finally, auralizations in various locations have been made. These auralizations are built around important centres of attention in the use of the church: the organ; the choir; and the reading of a church service from the presbytery.